Increased renal secretion of norepinephrine and prostaglandin E2 during sodium depletion in the dog. - Oliver, J A (1980)
To determine whether vasoactive renal hormones modulate renal blood flow during alterations of sodium balance, simultaneous measurements of arterial and renal venous concentrations of norepinephrine and prostaglandin E2 (PGE2) and of plasma renin activity, as well as renal blood flow and systemic hemodynamics were carried out in 24 sodium-depleted and 28 sodium-replete anesthetized dogs. The mean arterial blood pressure of the sodium depleted dogs was not significantly different from that of the animals fed a normal sodium diet, but cardiac output was significantly lower (3.07 +/- 0.18 vs. 3.77 +/- 0.17 liters/min, mean +/- SEM; P < 0.01). Despite the higher total peripheral vascular resistance in the sodium-depleted dogs (46.1 +/- 2.9 vs. 37.0 +/- 2.1 arbitrary resistance U; P < 0.02), the renal blood flow and renal vascular resistance were not significantly different in the two groups. The arterial plasma renin activity and concentration of norepinephrine were higher in the sodium-depleted animals than in the controls; the arterial concentration of PGE2 was equal in both groups. The renal venous plasma renin activity was higher in the sodium-depleted dogs. Similarly, the renal venous norepinephrine concentration was higher in the sodium-depleted dogs than in the controls (457 +/- 44 vs. 196 +/- 25 pg/ml; P < 0.01); renal venous PGE2 concentration was also higher in the sodium depleted dogs (92 +/- 22 vs. 48 +/- 11 pg/ml; P < 0.01). Administration of indomethacin to five sodium-replete dogs had no effect on renal blood flow. In five sodium-depleted dogs indomethacin lowered renal blood flow from 243 +/- 19 to 189 +/- 30 ml/min (P < 0.05) and PGE2 in renal venous blood from 71 +/- 14 to 15 +/- 2 pg/ml (P < 0.02). The results indicate that moderate chronic sodium depletion, in addition to enhancing the activity of the renin-angiotensin system, also increases the activity of the renal adrenergic nervous system and increases renal PGE2 synthesis. In sodium-depleted dogs, inhibition of prostaglandin synthesis was associated with a significant decrease in renal blood flow. The results suggest that the renal blood flow is maintained during moderate sodium depletion by an effect of the prostaglandins to oppose the vasoconstrictor effects of angiotensin II and the renal sympathetic nervous system.